Ideas of labour and moral education in the works of Zhambyl Dzhabayev. (Journal of Educational Sciences, 2016)
In the article the authors describe the work Jambul Dzhabayev as an inexhaustible source of meaningful and highly ideological poetic works in praise of labor as the basis of life. Indicates the ability of the Kazakh akyn to think imaginatively modern phenomena of social life, convey your thoughts bright, juicy vernacular. According to the authors, the works of the great bard has gained popularity not only in Kazakhstan but in the whole Soviet Union, his works have become a powerful means of education and training of young people. By analyzing lines of verse of the great elder, the authors prove that the Kazakh poet lays a powerful educational charge in their works, encouraging young people to love the Motherland, to develop patriotism, to link their fate with the fate of his people. Theauthors also cite the lines of the poet, where the poet awakens in young people an active start, recalls the need to defend their country from enemies. Jambul instills the idea that every person is part of society, be realized physically and spiritually to the greatest extent, according to him, by working for the good of the country, homeland and nation. PatriotismJambul is inseparable from the brotherhood of Nations, friendship and internationalism,that’s exactly what he’s singing in his soulful songs. The ultimate goal of human existence, according to Jambul, is to serve the people, to be principled, incorruptible honest. This life line gives the bard the ability to walk straight, not afraid of anything, preserving their dignity.
Keywords: upbringing; labor; morality; nation; equality.